Economics of development theory and evidence - Thirlwall, A. P.; Thirlwall, A. P. (Basingstoke, [England] Palgrave Macmillan, 2011)
"For nearly forty years, Thirlwall's texts have offered students a clear, comprehensive and rigorous overview of the economic aspects of growth and development. Now, this ninth edition of Thirlwall's popular textbook represents the most thorough revision to date of the author's classic textbook, Growth and Development: The new edition will continue to educate countless students interested in the topic. New to this edition:* All material, including data, has been brought up to date * New two-color text design makes it more accessible * New cases have been added throughout the text, including cases discussing the World Bank Commission on Growth and Development, and the technological divide * New sections on climate change and trade liberalization * Pedagogical tools such as case examples and discussion questions which support students in understanding and reflecting on theory"--Provided by publisher.
PART 1 - DEVELOPMENT AND UNDERDEVELOPMENT -- The Study of Economic Development -- The Development Gap and the Measurement of Poverty -- The Characteristics of Underdevelopment and Structural Change -- The Role of Institutions in Economic Development -- Theories of Economic Growth: Why Growth Rates Differ between Countries -- PART 2 - FACTORS IN THE DEVELOPMENT PROCESS -- The Role of Agriculture and Surplus Labour for Industrialisation -- Capital Accumulation, Technical Progress and Techniques of Production -- PART 3 - PERPETUATION OF UNDERDEVELOPMENT -- Dualism, Centre-periphery Models and the Process of Cumulative Causation -- Population and Development -- PART 4 - THE ROLE OF THE STATE, THE ALLOCATION OF RESOURCES, AND SUSTAINABLE DEVELOPMENT -- Resource Allocation in Developing Countries: The Market Mechanism and the Role of the State -- Project Appraisal, Social Cost-benefit Analysis and Shadow Wages -- Development and the Environment -- PART 5 - FINANCING ECONOMIC DEVELOPMENT -- Financing Development from Domestic Resources -- Foreign Assistance, Aid, Debt and Development -- PART 6 - INTERNATIONAL TRADE, THE BALANCE OF PAYMENTS AND DEVELOPMENT -- Trade Theory, Trade Policy and Economic Development -- The Balance of Payments, International Monetary Assistance and Development -- References and Further Reading.
Rev. ed. of: Growth & development, with special reference to developing economies / A.P. Thirlwall. 8th ed.
Keywords: Economic development; Developing countries -- Economic conditions